Determinants of recovery time from severe acute malnutrition among cholera-exposed and unexposed children in Ethiopia: a prospective cohort study - Alamneh, Alemayehu Belay; Abate, Kalkidan Hassen; Assaye, Ashagre Molla; Demlie, Yeshambel Worku; Guma, Moti Edosa; Belachew, Tefera (Frontiers in Nutrition, 2024)
Background: There is a vicious interplay between severe acute malnutrition (SAM) and diarrheal diseases including cholera. The lack of sufficient evidence on the time to recovery and its determinants among children with cholera prompted this investigation. The study aimed to evaluate the time to recovery and determinants among children with severe acute malnutrition, comparing cholera-exposed and unexposed children.A prospective cohort study was carried out from September 10, 2022, to February 21, 2023, among 224 children below 15 years. The study was conducted at cholera treatment centers and nearby communities in the Bale and Guji Zones of Oromia Regional state in Ethiopia. A structured questionnaire was used to obtain information and anthropometric measurements were conducted weekly. After checking all assumptions, a multivariable Cox Proportional Hazards model was used to identify independent determinants of time to recovery using an adjusted hazard ratio (AHR) with a 95% confidence interval (CI). Statistical significance was declared at P< 0.05.Results: Nearly 80% of participants recovered from SAM with a recovery rate of 40/1000 person-week observation and a median time to recovery of 21 days [Inter Quartile Range14-28]. The recovery time from SAM for cholera-exposed children was delayed by 54% [ARR: 0.46, 95% CI: 0.30-0.69] compared to unexposed children. Similarly, the recovery time from SAM for food-insecured families was delayed by 39% [ARR: 0.61, 95% CI: 0.38-0.96] compared to food-secured families. Moreover, children with more than three meal frequencies per day had 1.61 times [ARR: 1.61, 95% CI: 1.04-2.50] higher probability of fast recovery from SAM, compared to children with less than three meals. Children from families with good attitudes toward nutrition had more than two times [ARR: 2.23, 95% CI: 1.45-3.41] higher probability of faster recovery from SAM than families with poor attitudes.The study revealed that cholera exposure is one of the main determinants of prolonged recovery time for children with SAM. Food insecurity, meal frequency, and the attitude of parents toward children's dietary habits were determinants for the recovery of children from SAM. The findings imply the need for designing interventions to enhance child feeding during cholera illness, focusing on key determinants.